Composição química e bioatividade de óleos essenciais de lamiáceas para Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) e seletividade para Trichogramma pretiosum (Riley, 1879) (Hymenoptera: Trichogrammatidade) - Bibiano, Camila Silva (2019)
Species from the Lamiaceae family present natural substances in their secondary metabolism, such as essential oils (EO), which have high antifungal, bactericidal, and insecticidal bioactivity. These natural substances are promising alternatives to synthetic insecticides since they make it difficult for resistant populations to emerge due to their molecular complexity. However, the studied product must meet the requirements of target pest control efficiency and present low toxicity to beneficial organisms. The objective of this work was to study species from the Lamiaceae family and evaluate the chemical composition and bioactivity of their essential oils against Spodoptera frugiperda Smith, 1797 (Lepidoptera: Noctuidae), as well as their effects on the development of Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae). We selected six species belonging to the Lamiaceae family (Hyptis marrubioides Epling (Tubiflorae: Lamiaceae), Nepeta cataria L., Ocimum basilicum L. (Lamiales: Lamiaceae), Origanum majorana L., Origanum vulgare L., and Plectranthus amboinicus) from the Medicinal Plants Garden of the Universidade Federal de Lavras, in Lavras, Minas Gerais, Brazil. These plants were selected based on literature reviews of studies previously conducted with species of the same family which showed potential insecticide properties. Among the six species, four presented high insecticide potential, among which were O. basilicum and H. marrubioides, selected for their higher yields of essential oil when compared to the others. We found a 24-hour TL50 and a cumulative survival of 0.54% for the dosage of 70 µg/µL of O. basilicum EO. We identified linalool (39.49%) and 1,8-cineol (15.04%) as the major substances. In contrast, the dosage of 70 µg/µL of H. marrubioides EO showed a TL50 equivalent to 20.5 h and 0% cumulative survival, presenting β-thujone (41.49%) and α-thujone (15.81%) as major substances. Topical tests conducted with both selected species proved the insecticidal activity of these EOs for S. frugiperda. The results with the isolated majority substances suggest a synergy as a result of insecticide activity. The EOs of both species showed low toxicity to the T.pretiosum parasitoid.